Experimental Infection of Japanese Encephalitis Virus in Dogs - SHIMODA, Hiroshi; TAMARU, Seiji; MORIMOTO, Masahiro; HAYASHI, Toshiharu; SHIMOJIMA, Masayuki; MAEDA, Ken (Journal of Veterinary Medical Science, 2011)
A previous serosurvey of Japanese encephalitis virus (JEV) among dogs suggested that dogs are well suited for use as sentinels for assessing the risk of JEV transmission to humans. To examine the clinical symptoms and duration of anti-JEV antibodies in dogs, three dogs were experimentally challenged with JEV. All JEV-infected dogs did not show any clinical signs or abnormal blood tests, except for C-reactive protein. Virus-neutralization titers rapidly increased and were maintained until 70 days postinfection, and neither the virus nor the viral genome was detected in blood. Thus, since dogs live in close proximity to humans as companion animals, they are well suited for use as sentinels for surveying the human risk of JEV infection.